2019
DOI: 10.1371/journal.pone.0217698
|View full text |Cite
|
Sign up to set email alerts
|

Innovative DIEP flap perfusion evaluation tool: Qualitative and quantitative analysis of indocyanine green-based fluorescence angiography with the SPY-Q proprietary software

Abstract: Background Perfusion-related complications remain the most common concern in DIEP flap breast reconstruction. Indocyanine green-based fluorescence angiography can be used for the real-time intra operative assessment of flap perfusion. The SPY Elite system is the most widely used device in this setting. The main objective was to describe the use of SPY-Q proprietary software to perform qualitative and quantitative analysis of flap perfusion. Methods This retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Fluorescent imaging was quantitatively reported in 15 articles, including 515 patients [ 6 , 7 , 10 , 13 , 17 , 19 , 22 , 23 , 36 , 37 , 46 , 51 , 52 , 53 , 57 ]. The fields of application included free-flap and DIEP flap perfusion, breast reconstruction surgery, and microvascular surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent imaging was quantitatively reported in 15 articles, including 515 patients [ 6 , 7 , 10 , 13 , 17 , 19 , 22 , 23 , 36 , 37 , 46 , 51 , 52 , 53 , 57 ]. The fields of application included free-flap and DIEP flap perfusion, breast reconstruction surgery, and microvascular surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the peroperative use of ICG-A, 11 studies evaluated mastectomy flaps [21][22][23][24][25][26][27][28][29][30][31] , 10 studies evaluated autologous flaps [32][33][34][35][36][37][38][39][40][41] , and 5 studies included both implant-based and autologous breast reconstructions [42][43][44][45][46] .…”
Section: Included Studies and Study Characteristicsmentioning
confidence: 99%
“…Of the 10 studies on autologous breast reconstruction [32][33][34][35][36][37][38][39][40][41] , 1 study found that ICG-A significantly lowered the incidence of major complications in immediate reconstructions 32 , while 5 studies described an association between ICG-A and a reduced risk of fat necrosis 33 , 34 , 38-40 . Though ICG-A was applied for flap design and arterial mapping of DIEP flap perfusion 36 , 37 , 41 , 1 study found no benefit in using ICG-A on the recipient site 35 and finally 1 study found no association between flap perfusion and perforator anatomy 37 .…”
Section: Autologous Breast Reconstructionmentioning
confidence: 99%
“…There are a variety of methods by which surgeons are able to evaluate tissue perfusion. Indocyanine green angiography provides real-time feedback on perfusion, providing the surgeon with valuable information when evaluating free and pedicled flaps 41. Recent studies have demonstrated that this imaging modality is helpful in the assessment of flap harvesting and design, and quantitative and objective perfusion parameters seem to be accurate for flap perfusion assessment 41.…”
Section: Use Of Tracers In Gynecologic Cancer Treatment and Carementioning
confidence: 99%
“…Indocyanine green angiography provides real-time feedback on perfusion, providing the surgeon with valuable information when evaluating free and pedicled flaps 41. Recent studies have demonstrated that this imaging modality is helpful in the assessment of flap harvesting and design, and quantitative and objective perfusion parameters seem to be accurate for flap perfusion assessment 41. According to a recent investigation, indocyanine green angiography is a highly valuable tool in aiding flap shaping according to optimal perfusion zones42 (Figure 3).…”
Section: Use Of Tracers In Gynecologic Cancer Treatment and Carementioning
confidence: 99%